Dual Functions of the C5a Receptor as a Connector for the K562 Erythroblast-Like Cell-THP-1 Macrophage-Like Cell Island and as a Sensor for the Differentiation of the K562 Erythroblast-Like Cell during Haemin-Induced Erythropoiesis - Hiroshi Nishiura; Rui Zhao; Tetsuro Yamamoto (Clinical and Developmental Immunology)
The transcriptional nuclear factor binding to the Y box of human leukocyte antigen genes (NF-Y) for the C5a receptor (C5aR) gene is active in erythroblasts. However, the roles of the C5aR in erythropoiesis are unclear. We have previously demonstrated that apoptotic cell-derived ribosomal protein S19 (RP S19) oligomers exhibit extraribosomal functions in promoting monocyte chemotaxis and proapoptosis via the C5aR without receptor internalisation. In contrast to the extraribosomal functions of the RP S19, a proapoptotic signal in pro-EBs, which is caused by mutations in the RP S19 gene, is associated with the inherited erythroblastopenia, Diamond-Blackfan anaemia. In this study, we detected C5aR expression and RP S19 oligomer generation in human erythroleukemia K562 cells during haemin-induced erythropoiesis. Under monocell culture conditions, the differentiation into K562 erythrocyte-like cells was enhanced following the overexpression of Wild-type RP S19. Conversely, the differentiation was repressed following the overexpression of mutant RP S19. An RP S19 oligomer inhibitor and a C5aR inhibitor blocked the association of the K562 basophilic EB-like cells and the THP-1 macrophage-like cells under coculture conditions. When bound to RP S19 oligomers, the C5aR may exhibit dual functions as a connector for the EB-macrophage island and as a sensor for EB differentiation in the bone marrow.